Study guides

Q: How can you make 3 2 6 4 2 equals 7?

Write your answer...

Submit

Related questions

(9+3) - (2 +4) = 6

Yes, the simple equatoin is 5+4-3-2-1=3.

2*3*4 = 24

Yes, because 3 out of 4 equals 75% and 2 out of 3 equals 66.66%

8 to the power (2/3) equals 4.

Well, now isn't 2 plus 2 equals 42 times 2 equals 42 times 2 equals 2 plus 2 equals 42 times -2 equals 2 plus -2 equals 0 WAIT 2 times -2 equals negative 4 according to mathematics. No teacher nor professor has been able to even do more than stutter explaining this.3 times 3 equals 93 times -3 equals -9So why is the digit 2 different?

You would do it it by oppisites. 3+2+4=9 which equals C.

2/5 divided by 3/10 equals .4/.3 which equals 4/3 or 1.33333333

Equals 4, Not 32 + 2 equals 4, not 3.No, 2 plus 2 is 4.

1

9

The missing number is 49. This is why: 1 plus 2 equals 3, then 3 squared is 9. 2 plus 3 equals 5, then 5 squared is 25. Therefore, the missing number must be 49 to make the number sentence (3 plus 4 equals 7, then 7 squared is 49) true.

3/4 + 1/2 = 3/4 + 2/4 = 5/4 or 1 1/4 or 1.25

2/3 = 4/6

No.

2/3 plus 4/6 equals 1 1/3. 2/3 has the same value as 4/6 so in effect you are adding 4/6 and 4/6 together, which equals 8/6 or 1 1/3.

2 / 4 = 2 * 3 / 4 * 3 = 6 / 12

If x/2 +3 = 4 then x = 2

3+4*8/2 = 3+4*4 = 3+16 = 19

24 plus 61 plus 3 equals 88

2+2=4 3+1=4 etc.

6+4+3=2 when it is a mistake

wrong 4 equals a good time

You don't need to put any in as BODMAS tells you to do the multiplication first, but to clarify this you can put them around the multiplication: 2 + -3 x 4 = 2 + (-3 x 4)

Tacos!